O aborto entre os posicionamentos católicos, o feminismo e a legalidade jurídica - Costa, Iêda Rubens (2012)
The thesis aims to analyze how abortion is seen in the Brazilian society from the Catholic Church and feminist organizations. Therefore, the present analysis will be supported by the concepts of biopower and relative autonomy, in order to understand How both groups play historically crucial roles in this debate. Trying to prove this assumption, we will further analyze the positions of the National Conference of Bishops of Brazil and the feminist organizations, seeking the approval or disapproval of Complaint of breach of fundamental precept 54 and National Plan of Human Rights and bills in defense of the rights of the unborn.